9, 9′-Spirobifluorene based zinc coordination polymers: a study on linker geometry and topology. Issue 2 (12th December 2019) - Moreau, Florian; Audebrand, Nathalie; Poriel, Cyril
Abstract : We report four Zn-based coordination polymers (CPs), synthesized from three spirobifluorene (SBF) tetracarboxylate ligands, possessing different topologies and dimensionalities. Abstract : We report four Zn-based coordination polymers (CPs), synthesized from three spirobifluorene (SBF) tetracarboxylate ligands, possessing different topologies and dimensionalities. Zn-SBF- 1, Zn-SBF- 2 and Zn-SBF- 3 CPs have 2D crystal structures with an sql topology built from square planar ligands (L1 and L3 ) and paddle-wheels for Zn-SBF- 1 or original dimers of zinc for Zn-SBF- 2 and Zn-SBF- 3 . Zn-SBF- 4 is built from a ligand with a distorted tetrahedral geometry (L2 ) and an inorganic octahedral building unit resulting in a non-interpenetrated 3D porous framework with a toc topology. Structural relationships evidence that the meta (L2 ) versus para (L1 and L3 ) position of the carboxylic functions on the benzoate group of the SBF ligand increases the connectivity of the inorganic building unit and then the dimensionality of the framework.